Single cell transcriptome sequencing indicates the cellular heterogeneity of small intestine tissue in celiac disease - Tian Shi; Yan Feng; Jin Ma; Weidong Liu; Na Li; Ting Li; Adilai Abudurexiti; Ailifeire Tuerxuntayi; Shenglong Xue; Feng Gao (Scientific Reports)
Abstract Celiac disease (CeD) is an autoimmune small intestinal disease caused by gluten protein ingestion by genetically susceptible individuals. Genome-wide association studies and transcriptomic data have limited capacity to capture intercellular genetic variations. We aimed to construct a single cell transcriptome spectrum, analyze the immune microenvironment and cellular heterogeneity, discover disease-related specific genes and markers, and explore the pathogenesis of CeD. This study performed single cell RNA sequencing (scRNA-seq) on three small intestine biopsies from patients with CeD and three matched healthy Chinese controls. Immunohistochemistry (IHC) and quantitative polymerase chain reaction (qPCR) were used to validate potential diagnostic biomarkers of disease-differential genes. A total of 10 cell subpopulations were annotated, including three types of epithelial and stromal cells and seven types of immune cells. IHC revealed a pronounced overexpression of T cell disease-differential genes, TRAT1, BCL11B, and ETS1 in intraepithelial lymphocytes in the CeD group. Further clinical validation using qPCR confirmed that ETS1 (P = 0.010), TRAT1 (P < 0.001), and BCL11B (P = 0.036) were enriched in the CeD small intestinal tissue. The CD28/CTLA-4 pathway regulates the homeostasis of Treg cells. The IFITs family genes may serve as marker genes for antiviral specific CD4+ T cell subsets. CeD-derived subsets of CD8+ T cells frequently express genes associated with cytotoxicity, including IFNG, GZMK, GZMH, GZMB, SH2D1A, PRF1, and NKG7, as well as genes related to T cell exhaustion, such as PDCD10, CTLA4, TIGIT, PDCD1, and DUSP4. Inflammation and infection pathways were enriched in different cell populations. A single cell expression profile of CeD small intestinal tissue was successfully constructed using scRNA-seq in this study. New biomarkers for CeD-specific histopathology and potential therapeutic targets were discovered, and the biomarkers observed between inflammation and infection pathways were closely related to the onset of CeD.